EXPLOITING ELECTRONISATION POTENTIAL TO SPEED UP THE LITHUNIAN CIVIL PROCESS - Nekrošius, Vytautas; Simaitis, Rimantas; Vėbraitė, Vigita; Brazdeikis, Aurimas (Teisė, 2015)
Drawing on the comparative analysis and the recommendations and research of the Committee of Ministers of the Council of Europe and other institutions of the Council of Europe, the authors of the article outline the possibilities for electronisation of the civil process and a course of action to speed up the process and enhance its efficiency. The article goes on to identify key successful applications of such technologies. In addition, it highlights and describes the main features of the internationally recognised “best practice” examples in Austria, Finland and England.The article covers primary issues and challenges involved in the application of ICT in judicial processes and ways to deal with and overcome such issues.Based on such insights, the article explores the progress in electronisation of the civil process achieved so far in Lithuania in terms of exploiting the potential of speeding up the process, gives proposals for smoother development and implementation of ICT technologies in Lithuania.The authors recognise that the maximum effect in speeding up and improving the civil process can be achieved through the use of conveniently and attractively delivered and installed ICT technologies of all levels intended for application in courts (basic technologies and those intended for the administration and organisation of court activities and assistance to judges). For the purpose of ensuring that ICT potential is exploited smoothly and efficiently, adequate attention must be given and sufficient funds must be allocated towards a revolutionary transition from a paper-based judicial infrastructure to the informational infrastructure, which is based on electronic information and electronic documents.As to Lithuania, a conclusion is made that during the past several years there has been significant progress in the use of ICT to speed up the Lithuanian civil process. Public electronic services have been enabled and are being developed further, a full switch has been made from classical recording of court hearings to digital sound recording and the use of video conferencing tools, a bold and determined transition to the informational judicial infrastructure has been started, and there are plans for continued large-scale modernisation of the Lithuanian judicial information system. The problems faced in Lithuania while implementing ICT in judicial processes are practically the same as elsewhere – lack of financing, conservative approach, lack of openness to novelty, insufficient attention to managing the “human factor” issue. In order to ensure that such problems are tackled efficiently, the authors recommend continuous monitoring of the economic and qualitative benefits that the progress of electronisation of the civil process brings, ensuring flexible implementation of more ergonomic and effective measures which better meet user expectations, making more intensive and determined efforts to develop the informational infrastructure of court activities, doing more precise and clear strategic planning, determining more optimally and aligning the priorities of the projects for ICT development in courts, and taking the courage to adapt more flexibly the classical standards of the process while implementing ICT. Ultimately such change helps to ensure the right of individuals to more expeditious, fair and proper justice.